Structural analysis of the 5' flanking region of the beta-globin gene in African sickle cell anemia patients: further evidence for three origins of the sickle cell mutation in Africa. - Chebloune, Y (1988)
Haplotype analysis of the beta-globin gene cluster shows two regions of DNA characterized by nonrandom association of restriction site polymorphisms. These regions are separated by a variable segment containing the repeated sequences (ATTTT)n and (AT)xTy, which might be involved in recombinational events. Studies of haplotypes linked to the sickle cell gene in Africa provide strong argument for three origins of the mutation: Benin, Senegal, and the Central African Republic. Nevertheless, the haplotype determination does not give any information about the variable segment and does not totally exclude the possibility of recombination leading to different haplotypes linked to the mutation. The structure of the variable segment in the three African populations was studied by S1 nuclease mapping of genomic DNA, which allows a comparison of several samples. A 1080-base-pair DNA segment was sequenced for one sample from each population. S1 nuclease mapping confirmed the homogeneity of each population with regard to both (ATTTT)n and (AT)xTy repeats. We found three additional structures for (AT)xTy correlating with the geographic origin of the patients. Ten other nucleotide positions, 5' and 3' to the (AT)xTy copies, were found to be variable when compared to homologous sequences from human and monkey DNAs. These results allow us to propose an evolutionary scheme for the polymorphisms in the 5' flanking region of the beta-globin gene. The results strongly support the hypothesis of three origins for the sickle mutation in Africa.